ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK UMKM DALAM MEMBAYAR PAJAK DI KPP PRATAMA SURABAYA MULYOREJO - Yunita Setiawati; Yulia Setyarini (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2023)
Taxes play a very important role in state life, so the government makes various efforts to increase state income. One way is by implementing an independent statistical system, but this also makes tax revenues very dependent on taxpayers' awareness and compliance with their tax obligations. Therefore, this research aims to determine the factors that influence taxpayer performance. This research is quantitative research. The sample used in this research is MSME taxpayers who pay taxes to KPP Pratama Mulyorejo in Surabaya. The sampling method is random sampling. The number of small, medium and micro business taxpayers who filled out the questionnaire was 100 people. The results of this research show that variables such as tax awareness, knowledge and understanding of tax regulations, tax rates, and tax audits have an impact on MSME taxpayer compliance, while tax authorities and tax sanctions have an impact on MSME compliance.